SPECIFIC CHARACTERISTICS OF THE STATE ADMINISTRATION SYSTEM IN THE KHANATE OF KHIVA - Xayitboyeva Muhayyo (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This scientific article is devoted to the study of the state administration system of the Khanate of Khiva, which held a significant political and economic position in the Central Asian region from the 17th century to the early 20th century. The article analyzes the central and local administrative structures of the khanate, the political hierarchy, and the specific characteristics of the state apparatus. The research highlights the synthesis of the "Uzbek nomadic pastoralist" (chorva) and "sedentary agricultural" (otrok dehqonchilik) traditions in state governance, as well as the role of Islamic law (Sharia) and Turco-Mongol traditions within the administrative system. The content of the article illustrates the khan as an absolute ruler, while also examining the authorities of the Council under his rule and its high-ranking officials, such as the qushbegi and devonbegi, based on archival documents and historical sources. Furthermore, the study scientifically substantiates the interdependence of the administrative-territorial division, the taxation system, and military administration, exploring how the unique geographical location of the Khwarazm oasis influenced this governance model. In conclusion, the administrative system of the Khanate of Khiva is evaluated within the context of Oriental statehood of that era.